USING “ALIBI GAME” TO TEACH ORAL RECOUNT TEXT TO SENIOR HIGH SCHOOL STUDENTS - Mella Wiani Putri; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2016)
Speaking skills in learning is a priority for teaching English of foreign learners. Most of students still have difficulties in speaking English related with the correct forms and rules of grammar and tenses, so that the appropriate technique of teaching and learning is needed to solve the students’ problems. ”Alibi Game” is a game which aimed to improve students’ speaking ability, especially in telling the chronological event in oral recount text. In implementing this game, at the beginning of the lesson, the teacher has to introduce the topic that will be learned. The teacher then explains the material about recount in general before getting into the game. Alibi game has 3 parts that help students’ problems in oral recount. They are discussion, interrogation and conclusion parts. The process of the game requires students to tell in past tense which is the language feature of recount.